2017
DOI: 10.3389/fpls.2017.00631
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of Lower Brachyceran Flies (Diptera) and Their Adaptive Radiation with Angiosperms

Abstract: The Diptera (true flies) is one of the most species-abundant orders of Insecta, and it is also among the most important flower-visiting insects. Dipteran fossils are abundant in the Mesozoic, especially in the Late Jurassic and Early Cretaceous. Here, we review the fossil record and early evolution of some Mesozoic lower brachyceran flies together with new records in Burmese amber, including Tabanidae, Nemestrinidae, Bombyliidae, Eremochaetidae, and Zhangsolvidae. The fossil records reveal that some flower-vis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 54 publications
0
6
0
Order By: Relevance
“…Regardless of whether wings were present or absent in the common ancestor of Euphasmatodea, our results show an increase in diversification rate with the start of their radiation (Supplementary file 11). This rapid radiation that largely follows the Cretaceous-Palaeogene (K-Pg) mass extinction (~66 mya) was previously suggested to be linked to the diversification of flowering plants 53 -a co-evolutionary pattern also observed in other plantassociated insect groups [80][81][82] . Our results substantiate this hypothesis, particularly, when considering the results of the trait-dependent diversification analysis (HiSSE) from which we concluded that flight or flightlessness might not have been the main driver of euphasmatodean diversification.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Regardless of whether wings were present or absent in the common ancestor of Euphasmatodea, our results show an increase in diversification rate with the start of their radiation (Supplementary file 11). This rapid radiation that largely follows the Cretaceous-Palaeogene (K-Pg) mass extinction (~66 mya) was previously suggested to be linked to the diversification of flowering plants 53 -a co-evolutionary pattern also observed in other plantassociated insect groups [80][81][82] . Our results substantiate this hypothesis, particularly, when considering the results of the trait-dependent diversification analysis (HiSSE) from which we concluded that flight or flightlessness might not have been the main driver of euphasmatodean diversification.…”
Section: Discussionmentioning
confidence: 86%
“…Previous authors argued that the probability or cost ratio of wing gain was considered too high compared with that of its loss 40 . In our reconstruction, the estimated number of potential regains ranges between 9 and 36 events (~22) with ~42 losses versus ~76 losses (71)(72)(73)(74)(75)(76)(77)(78)(79)(80)(81)(82) if wing loss is considered irreversible (Figure 5), hence, permitting re-evolution appears to be more parsimonious. For instance, in predominantly wingless Diapheromerinae, we find 1-3 potential wing regain events versus an alternative of a total of ten losses if wing recovery was impossible.…”
Section: Discussionmentioning
confidence: 99%
“…Diptera is one of the most successful groups of animals from both an evolutionary and ecological perspective [31][32][33], which likely relates to their ability to exploit a wide range of nutritional fluids. Our hypothesis was partially supported in that the morphology and certain aspects of the material properties of the prestomal teeth relate to feeding habits, but our hypothesis that the prestomal teeth have a high concentration of inorganic elements was not supported.…”
Section: Discussionmentioning
confidence: 99%
“…Animals and plants influenced each other generating some constraints and the driving force for their further coevolution (Pauw et al 2009;Zhang and Wang 2017). However, it is necessary taking into account that flowering plants and pollinators affect each other with different mechanisms.…”
Section: The Beauty Of Fooers As An Emergent Qualitymentioning
confidence: 99%